2019
DOI: 10.3389/fpsyg.2019.01669
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Recruitment: Communication Characteristics and Sought Gratifications

Abstract: This study examines how social media pages can be used to influence potential applicants’ attraction. Based on the uses and gratifications theory, this study examines whether organizations can manipulate the communication characteristics informativeness and social presence on their social media page to positively affect organizational attractiveness. Moreover, we examine whether job applicants’ sought gratifications on social media influence these effects. A 2 × 2 between-subjects experimental design is used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Organizations should incorporate social media into internal communication strategies and existing employee recruitment strategies (Aggerholm and Andersen, 2018;Ewing et al, 2019;Gibbs et al, 2015;Hunt, 2010;Villeda and McCamey, 2019). Prior research has focused on how organizations use social media to guide decision makingan organization using a candidate's social media account as part of the screening process, for instance (see Carpentier et al, 2019;Muduli and Trivedi, 2020;Slovensky and Ross, 2012). Though limited, there has been some scholarly work on the organizational use of social media employee recruitment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Organizations should incorporate social media into internal communication strategies and existing employee recruitment strategies (Aggerholm and Andersen, 2018;Ewing et al, 2019;Gibbs et al, 2015;Hunt, 2010;Villeda and McCamey, 2019). Prior research has focused on how organizations use social media to guide decision makingan organization using a candidate's social media account as part of the screening process, for instance (see Carpentier et al, 2019;Muduli and Trivedi, 2020;Slovensky and Ross, 2012). Though limited, there has been some scholarly work on the organizational use of social media employee recruitment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though limited, there has been some scholarly work on the organizational use of social media employee recruitment. For example, studies have found that using social media as an organizational branding tool results in improved organizational attractiveness (Carpentier et al, 2017) especially when the profiles include relevant job information (Carpentier et al, 2019). Social media can be a useful tool for improving an organization's image and application intentions (Kissel and B€ uttgen, 2015), corporate reputation (Sivertzen et al, 2013) and reaching younger applicants (Villeda and McCamey, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Building a social media community is an essential part of e-recruiting (Rodríguez-Sánchez et al, 2019). Sharing relevant information about daily life at a company improves an employer's attractiveness to candidates, especially when this content is delivered in a personable manner (Carpentier et al, 2019). Social media is a new communication channel between an employer and job applicants that can create a basic form of meaningful hiring communication (Aggerholm & Andersen, 2018).…”
Section: The Potential Of Social Media In Personnel Marketingmentioning
confidence: 99%
“…The empirical evidence seems to suggest that variables of different nature affect applicant perceptions of the selection process [11,14,17,18]: The applicant characteristics (e.g., work experience, personality, age) [32], perceptions of procedure characteristics (e.g., transparency, length of process, recruitment media) [33,34,35] and job characteristics (e.g., attractiveness, requirements) influence applicant reactions in terms of fairness and perceived procedural justice, which, in turn, influence applicant outcomes (in term of organisational recommendation, satisfaction, performance) [20], with potential outcomes in terms of future job identity [36].…”
Section: Rejection Procedures and Candidates’ Reactions About The Smentioning
confidence: 99%